The prevalence of mathematical difficulties among primary school children in Mainland China: a systematic review and meta-analysis - Wang, Yanjiao; Long, Jia; Wang, Pei (Frontiers in Public Health, 2024)
The prevalence of mathematical difficulties (MD) among primary school children in mainland China and its related factors remain unclear. To provide a suitable foundation for formulating appropriate screening and intervention strategies, this study aimed to estimate the prevalence of MD and its possible factors among primary school children in mainland China. Articles were identified from seven databases and included if they reported on the prevalence of MD among primary school children in mainland China. A total of 30,881 articles were retrieved, 975 of which were subjected to full evaluation.Fifty-four studies involving 34,815 participants (mean age 9.86±3.13 years) were included. Analyses were conducted using the Meta and Metafor packages in the statistical software environment R. We used meta-regression and subgroup analyses by variable type to evaluate the potential prevalence factors. The pooled prevalence of MD among primary school children in mainland China was 8.97%, whereas the prevalence rates of MD in lower, middle, and upper primary schools were 11.57%, 10.07%, and 4.76%, respectively. The results showed that the prevalence of MD among primary school children in mainland China was significantly related to grade level and cut-off points selected for screening MD, and that the prevalence of MD in middle primary school was higher in girls than in boys. The prevalence of MD in primary schools in mainland China was slightly higher than that in countries such as the United Kingdom and the United States. The prevalence of MD was higher in the lower and middle grades of primary school. The grade level and cut-off points selected during MD screening were closely related to the prevalence of MD. More attention should be paid to girls with MD in middle primary school.